(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
Wheat blast (Magnaporthe oryzae Triticum) in Bangladesh and South America is recognized as one major limiting factor of wheat production. Its control using chemical pesticides raises concerns about food safety and pesticide resistance, which have dictated the need for alternative blast management approach, nutrient supplementation could be an ecofriendly alternative. Experiments were carried out under confined net house condition for two consecutive cropping seasons. Single doses of the nutrients (Si, B and Zn) were incorporated during soil preparation. Plants of the wheat blast susceptible variety BARI Gom-26 were inoculated with spores (1 x 107 spores ml-1) of Magnaporthe oryzae Triticum at blast vulnerable pre-heading stage of 52 days age. Typical wheat blast symptoms of spike bleaching from top to downward appeared on sight 14 days after inoculation i.e., 66 days age of the crop. Incidence and severity of blast bleaching of spike were scored for four times starting from 68 days age @ three day’s interval. None of the nutrients could stop the incidence of blast on wheat; however, some nutrients reduced the blast incidence significantly. Solo application of Si, B and Zn or combination of two caused significant reduction of spike bleaching. With the mixed application of Si, B and Zn, > 47% reduction of wheat blast severity was obtained. The results revealed that the soil application of silicon, zinc and boron had a synergistic effect on the intensity of blast disease of wheat. Int. J. Agril. Res. Innov. Tech. 11(2): 76-84, Dec 2021